Fibronectin Affects Transient MMP2 Gene Expression through DNA Demethylation Changes in Non-Invasive Breast Cancer Cell Lines - Pereira, Isabela T.; Ramos, Edneia A. S.; Costa, Erico T.; Camargo, Anamaria A.; Manica, Graciele C. M.; Klassen, Liliane M. B.; Chequin, Andressa; Braun-Prado, Karin; de O. Pedrosa, Fábio; Souza, Emanuel M.; Costa, Fabricio F.; Klassen, Giseli (PloS one, 2014)
Metastasis accounts for more than 90% of cancer deaths. Cells from primary solid tumors may invade adjacent tissues and migrate to distant sites where they establish new colonies. The tumor microenvironment is now recognized as an important participant in the signaling that induces cancer cell migration. An essential process for metastasis is extracellular matrix (ECM) degradation by metalloproteases (MMPs), which allows tumor cells to invade local tissues and to reach blood vessels. The members of this protein family include gelatinase A, or MMP-2, which is responsible for the degradation of type IV collagen, the most abundant component of the basal membrane, that separates epithelial cells in the stroma. It is known that fibronectin is capable of promoting the expression of MMP-2 in MCF7 breast cancer cells in culture. In addition, it was already shown that the MMP2 gene expression is regulated by epigenetic mechanisms. In this work, we showed that fibronectin was able to induce MMP2 expression by 30% decrease in its promoter methylation. In addition, a histone marker for an open chromatin conformation was significantly increased. These results indicate a new role for fibronectin in the communication between cancer cells and the ECM, promoting epigenetic modifications.